Exploring the relationship between environmental enteric dysfunction and oral vaccine responses. - Church,JA; Parker,EP; Kosek,MN; Kang,G; Grassly,NC; Kelly,P; Prendergast,AJ (Future Microbiology, 2018)
Oral vaccines significantly underperform in low-income countries. One possible contributory factor is environmental enteric dysfunction (EED), a subclinical disorder of small intestinal structure and function among children living in poverty. Here, we review studies describing oral vaccine responses and EED. We identified eight studies evaluating EED and oral vaccine responses. There was substantial heterogeneity in study design and few consistent trends emerged. Four studies reported a negative association between EED and oral vaccine responses; two showed no significant association; and two described a positive correlation. Current evidence is therefore insufficient to determine whether EED contributes to oral vaccine underperformance. We identify roadblocks in the field and future research needs, including carefully designed studies those can investigate this hypothesis further.